Transient antagonism of anti‐CD20 monoclonal antibodies and PI3K inhibitor idelalisib in DLBCL cell lines. (17th May 2018) - Zoellner, Anna‐Katharina; Peter, Nico; Zimmermann, Yvonne; Hutter, Grit; Hiddemann, Wolfgang; Dreyling, Martin
Abstract: Introduction: PI3K inhibitors are evaluated for relapsed and refractory Diffuse large B‐cell lymphoma (DLBCL) patients. Objective: As rituximab has shown to influence B‐cell receptor (BCR) signaling, we investigated the interaction of anti‐CD20 antibody rituximab and the new type II glycoengineered anti‐CD20 antibody obinutuzumab in combination with the PI3K delta inhibitor idelalisib. Methods: Established DLBCL cell lines were treated with either rituximab or obinutuzumab alone or in combination with PI3K delta inhibitor idelalisib. Results: Rituximab and to a lesser extent obinutuzumab monotherapy resulted in a temporary upregulation of p‐Akt, p42/44, and p38 signaling pathways. Idelalisib reduced p‐Akt expression. Rituximab antagonized the p‐Akt downregulation at early time points, while obinutuzumab did not interfere with idelalisib's effects. In cell growth analysis, early antagonism could also be detected. Conclusion: The combination of idelalisib with CD antibodies shows an initial antagonism of rituximab but not obinutuzumab in downregulation of PI3K‐signaling targets.